Từ STEM đến transdisciplinary learning: Xu hướng giáo dục tích hợp trên thế giới và một số khuyến nghị - Nguyễn, Minh Hồng (Tạp chí Giáo dục, 2025)
In the context of global education shifting strongly towards integration to meet the requirements of curriculum innovation and learner competence development in the 21st century, the article uses a qualitative design, combining the method of document analysis and comparative policy analysis to clarify three typical trends of integrated education in the world - STEM/STEAM, interdisciplinary, and transdisciplinary learning. Based on the theoretical analysis framework, the authors conducted a case study in Vietnam, focusing on the current state of policies, capacity of the program organization, and teaching staff in implementing integrated education models. Based on the findings from international analysis and domestic cases, the article proposes feasible reform recommendations, suitable for national conditions and sustainable development orientation. The research results contribute to providing academic and practical arguments for planning integrated education policies in Vietnam in the context of transforming the education system towards openness, flexibility, and competency orientation